- 20x²( 5x + 2y - 7z) = -100x² - 40x²y + 140 x²z
5(-3x + 12y - 4) = -15x + 60y - 20
- 2a( -[tex]\frac{1}{2}[/tex] + 3a ) = - 2a* [tex]\frac{1}{2}[/tex] * 2a *3a = -a + 2a * 3a = -a + 6a²
6xy (-2x + 4y - 7) = -12x²y + 24xy² - 42xy
m(-4m + 3n - 2) = -4m² + 3mn - 2m
[tex]\frac{2}{3}[/tex](6a - 12b + 9 ) = [tex]\frac{2}{3}[/tex] * 3(2a - 4b + 3) = 2(2a - 4b + 3) = 4a - 8b + 6
(-5x + 7y - 2z )x (-2) = (-5x + 7y - 2z) (-2x) = 10x² - 14xy + 4xz
ab(- 10a + 20b - 35 ) = -ab * 10a + ab * 20b - 35ab = -10a² + 20ab² - 35ab